(untitled) (Journal of Nuclear Technology in Applied Science, 2019)
The aim of the current study is to measure the entrance skin dose (ESD) for patients undergoing pelvic diagnostic X-ray examinations in King Faisal Specialist Hospital (KFH), Saudi Arabia, and reduce the scattered x-ray to gonads during the examination. The thermo-luminescence dosimeters (TLDs) are processed for low energy X-ray calibration. Three sets of thermo-luminescence dosimeters LiF (TLD-100) detector were irradiated by using a Xstrahl machine with following operating conditions: 60 cm FSD, 1 mA, irradiation time 1 min., 2 mm HVL(Al) and tube voltage of 80 kV. Each TLD set was irradiated for specific air and the mean value of the air kerma was used for calculation the calibration factor. The (ESD) was assessed for forty patients undergoing pelvic diagnostic X-ray examinations using thermo-luminescence dosimeters (TLDs). The patients were classified into three groups according to weights from 40-60 kg, 60-80 kg and 80-110 kg respectively. The ESDs associated with AP-pelvic examinations for the classified patients were 2.91 ± 0.25 mGy , 3.92 ± 0.22 mGy and 4.92 ± 0.6 mGy respectively. The results are compared with the reference levels of the European Union, (EU), International Atomic Energy Agency,(IAEA) and United Kingdom) . Another irradiation for TLD-100 chips was performed above and under the surface of the Lawrence Livermore National Laboratory phantom (LLNL, USA), and a scatter dose absorbed by sensitive organ attenuated by a factor of 20.6% due to using a flat contact gonadal shield .